Optimal design of electric bicycle (electric bicycle motor) - Ahmad Zainul Ariffin, Mohamad (2013)
The creation of Electric Bicycle gives many advantages in our lives. This thesis is focused on the type of motor that used on the electric bicycle, the type of motor that were used on the electric bicycle is Brushless DC (BLDC) motor. The BLDC motor provides many advantages to the electric bicycle, it provide lots of benefits to the user. It is not only for electric bicycle it can be used to lot of machines. By the way, the characteristic of BLDC motor make it majorly being used around the world, this is because it has high efficiency, long life duration and more durable compared to other motor. The BLDC motor were widely been used on most type of the electric bicycle which is most compatible with it. The used of BLDC motor on the bicycle give the bicycle maximum performances and can travel longer with certain level. Analysis that was done to this type of motor is to determine either this motor suitable for the electric bicycle or vice versa. The criteria that were analyze are, torque, speed, power, current and efficiency.